Pedagogical and Psychological Features in The Development of Spiritual and Moral Qualities of Future Doctors - Ravshan Alimjanovich Yunusov; Safarova Elmira Muqimjonovna; Safarova Elmira Muqimjonovna (Scientific Trends, 2024)
The problems of moral and spiritual education and personal development are considered in various organizational forms, using all possible means and methods, based on the use of diverse psychological, pedagogical and social technologies. The moral and spiritual development of a person depends on the nature of social conditions and upbringing, which are formed for the spiritualization and implantation of a person through psychological and pedagogical techniques into the socio-cultural space. The most important socio-psychological problem of moral character education is the formation of stable, dominant, and action-defining moral relationships.
Keywords: Medical university, moral and spiritual development, moral and spiritual development of personality, psychological and pedagogical recommendations.